Reducing the risks for substance abuse a lifespan approach - Daugherty, Raymond P.; Leukefeld, Carl G. 1943- (Plenum Press, 1998)
Since about 1980, substance abuse prevention programs have taken a youth-based, "zero-tolerance" approach. Significant increases in abstinence have followed, but so have simultaneous increases in high-risk use. Arguing that the basic assumptions of this approach are flawed, authors Raymond P. Daugherty and Carl Leukefeld offer a dynamic alternative: the Lifestyle Risk Reduction Model, which reshapes accepted alcohol and drug premises, messages, and strategies to make them relevant throughout the entire lifespan. It will prove to be a valuable resource to clinicians, teachers, and students in alcoholism studies, public health, health psychology, behavioral medicine, consulting and counseling psychology, and sociology.
Keywords: Alcoolisme - États-Unis - Prévention; Modification du comportement - États-Unis; Toxicomanie - États-Unis - Prévention; Étapes de la vie - États-Unis; Alcoholism -- prevention & control -- United States; Alcoholism -- United States -- Prevention; Behavior Therapy -- United States; Behavior modification -- United States; Drug abuse -- United States -- Prevention; Life Cycle Stages -- United States; Life cycle, Human -- United States; Substance-Related Disorders -- prevention & control -- United States; Gesundheitsvorsorge; Drogenabhängigkeit; Alkoholismus; Lebensalter; USA